Effect of layer number and layer stacking registry on the formation and quantification of defects in graphene. (March 2016) - Costa, Sara D.; Ek Weis, Johan; Frank, Otakar; Kalbac, Martin
Abstract: Correct defect quantification in graphene samples is crucial both for fundamental and applied research. Raman spectroscopy represents the most widely used tool to identify defects in graphene. However, despite its extreme importance the relation between the Raman features and the amount of defects in multilayered graphene samples has not been experimentally verified. In this study we intentionally created defects in single layer graphene, turbostratic bilayer graphene and Bernal stacked bilayer graphene by oxygen plasma. By employing isotopic labelling, our study reveals substantial differences of the effects of plasma treatment on individual layers in bilayer graphene with different stacking orders. In addition Raman spectroscopy evidences scattering of phonons in the bottom layer by defects in the top layer for Bernal-stacked samples, which can in general lead to overestimation of the number of defects by as much as a factor of two.